Disodium dihydrogen pyridine-2,3,5,6-tetracarboxylate trihydrate - Hu, Fang-Hong (International Union of Crystallography, 2010)
In the title compound, 2Na(+)·C(9)H(3)NO(8) (2−)·3H(2)O, the asymmetric unit consists of two Na(+) cations, one dihydrogen pyridine-2,3,5,6-tetracarboxylate dianion (H(2)pdtc(2−)) and three water molecules coordinated to the Na(+) cations. The configuration of the anion is stabilized by intramolecular O—H⋯O hydrogen bonding between vicinal carboxylate/carboxy groups. The Na(+) cations are bridged by the H(2)pdtc(2−) dianions, generating layers extending infinitely in sheets parallel to (001), and further pillared by the water molecule linkers to build up a three-dimensional framework.